Ziegfeld Girl : Image and Icon in Culture and Cinema - Mizejewski, Linda (Book collections on Project MUSE., 1999)
In the first decades of the twentieth century, Broadway teemed with showgirls, but only the Ziegfeld Girl has survived in American popular culture--as a figure of legend, nostalgia, and camp. Featured in Florenz Ziegfeld Jr.'s renowned revues, which ran on Broadway from 1907 to 1931, the Ziegfeld Girl has appeared in her trademark feather headdresses, parading and posing, occasionally singing and dancing, in numerous musicals and musical films paying direct or indirect homage to the intrepid producer and his glorious Girl. Linda Mizejewski analyzes the Ziegfeld Girl as a cultural icon and argues that during a time when American national identity was in flux, Ziegfeld Girls were both products and representations of a white, upscale, heterosexual national ideal.Mizejewski traces the Ziegfeld Girl's connections to turn-of-the-century celebrity culture, black Broadway, the fashion industry, and the changing sexual and gender identities evident in mainstream entertainment during the Ziegfeld years. In addition, she emphasizes how crises of immigration and integration made the identity and whiteness of the American Girl an urgent issue on Broadway's revue stages during that era. Although her focus is on the showgirl as a "type," the analysis is intermingled with discussions of figures like Anna Held, Fanny Brice, and Bessie McCoy, the Yama Yama girl, as well as Ziegfeld himself. Finally, Mizejewski discusses the classic American films that have most vividly kept this showgirl alive in both popular and camp culture, including The Great Ziegfeld, Ziegfeld Girl, and the Busby Berkeley musicals that cloned Ziegfeld's showgirls for decades. Ziegfeld Girl will appeal to scholars and students in American studies, popular culture, theater and performance studies, film history, gender studies, gay and lesbian studies, and social history.